Species Checklist of Fishes from Samunsam River in Samunsam Wildlife Sanctuary, Sarawak - Fazimah, Aziz; Jacqleen, Mik; Radin Azreena, Radin Shahrom; Anisa Grace, Robert Galang; Nurhanis Hafizah, Hanafiah; Mohd Asyraf, Sulaiman (UNIMAS Publisher, 2024)
The sampling was carried out at Sungai Samunsam, Samunsam Wildlife Sanctuary on the 4th to 8th November 2018. Six sampling sites were selected, which 3 sites were located in freshwater and 3 sites in brackish water. The fish samples were collected using three-layer gill nets. There was a total of 324 individuals of fish collected with Ariidae as the most dominant fish family (70.68%). Overall, 18 fish families with 23 fish species were identified.